Acute myeloneuropathy due to Glutaric aciduria-1: Expanding the phenotypic spectrum - Dipti Baskar; Rita Christopher; Gautham Arunachal; Davuluri Durga Srinivas Anudeep; Ambati Mounika; TA Sangeeth; Kiran Polavarapu; BS Shalini; Tarachand Joshi; Sai Bhargava Sanka; Saraswati Nashi; Pritam Raja; et al. (Global Medical Genetics)
Glutaric aciduria type-1 (GA-1) is a rare metabolic disorder due to mutation in GCDH gene resulting in varied clinical manifestations. Here we report a case of late-onset GA-1 with acute myelo-neuropathy and chronic renal failure. Institutional ethics committee approval was obtained and genetic analysis was done by clinical exome sequencing. Here we present 19 year-old-adolescent male with chronic renal disease for 2 years presented with 5 months history of sudden onset weakness of proximal and distal lower limbs and bladder retention. This was preceded by recurrent episodes of vomiting. On clinical examination he had features of myeloneuropathy. Laboratory evaluation showed significant elevation of blood glutaryl carnitine with very low free carnitine, while extensive white matter signal changes with diffusion restriction, subependymal nodules and involvement of internal capsule were evidenced on brain magnetic resonance imaging. Diagnosis was confirmed by clinical exome sequencing which showed a pathogenic homozygous missense mutation in exon 11 of GCDH gene (c .120 C>T, p.His403Tyr). This report expands phenotypic spectrum of GA-1 to include late onset acute myelo-neuropathy with chronic renal failure. A high index of suspicion is required since early treatment might decelerate further disease progression.